2021
DOI: 10.1111/cen.14440
|View full text |Cite
|
Sign up to set email alerts
|

Suppurative thyroiditis: Systematic review and clinical guidance

Abstract: Acute suppurative thyroiditis (AST) is a rare condition. The following factors are thought to make the thyroid relatively resistant to infection: the thyroid capsule, its rich blood supply and lymph drainage and its high iodine concentration. 1 The usual presentation of AST is with neck pain, fever, elevated white cell count (WCC), elevated ESR and at times hyperthyroidism, making it initially difficult to clinically distinguish from subacute thyroiditis (SAT), although patients with AST are often systemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 35 publications
1
47
0
1
Order By: Relevance
“… 9 Similar to previous studies, in our study, we observed that AST occurs in a slightly higher percentage of females. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Similar to previous studies, in our study, we observed that AST occurs in a slightly higher percentage of females. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The primary clinical manifestations of AST include neck pain, fever, dysphagia, dysphonia, and erythema. 10 Laboratory examinations may show leukocytosis and elevated ESR and CRP levels in some children without specific serum markers. 18 Thyroid function tests are usually normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscess should be aspirated and sent for culture and staining to assist in the diagnosis and choice of proper antimicrobial therapy, as well as for cytology to ensure that a malignancy has not been missed [ 11 ]. The aspirate should be stained for bacteria, fungi, and mycobacteria and cultured for aerobic and anaerobic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the predisposing factors, the most important is immunosuppression, followed by the presence of the pyriform sinus fistula, diabetes mellitus, and disseminated infection. Complications and sequelae include airway obstruction, dysphagia, esophageal perforation or fistula, Horner’s syndrome, an extension of the abscess resulting in mediastinitis, pericarditis, thrombophlebitis, sepsis, thyroid dysfunction associated with thyroiditis (hyper- or hypothyroidism), and death ( 32 ).…”
Section: Thyroid Diseasesmentioning
confidence: 99%